SCIENTIFIC AND THEORETICAL–METHODOLOGICAL FOUNDATIONS OF INFORMATION AND PSYCHOLOGICAL SECURITY IN OPEN INFORMATION SYSTEMS - B. Umarov (American Journals Publishing, 2025)
The rapid development of information and communication technologies has fundamentally transformed modern society, accelerated information flows and reshaping individual consciousness, social relations, and state governance. In the context of open information systems, information and psychological security has become one of the most critical challenges of the twenty-first century. This article explores the scientific, theoretical, and methodological foundations of information and psychological security within open information systems. Special attention is given to the dual nature of information as both a developmental resource and a potential source of psychological threats. The study analyzes the impact of intensive information environments on individual, social, and state stability, highlighting the role of mass media, digital platforms, and information warfare. The article also emphasizes the necessity of developing comprehensive socio-psychological, educational, and governance mechanisms to ensure resilience against destructive information influences and to protect national and human security in the global information space.
Keywords: Information security, psychological security, open information systems, information influence, mass media, information warfare, social stability